The Influence of Promotion and School Image on Parents' Decision in Choosing a School at SMP Muhammadiyah Merauke: Pengaruh Promosi dan Citra Sekolah terhadap Keputusan Orang Tua dalam Memilih Sekolah di SMP Muhammadiyah Merauke - Haryanti, Nur Lailly Enny; Rahmawati, Imelda Dian (Indonesian Journal of Innovation Studies, 2026)
General Background: Parents consider multiple factors when selecting schools amid increasing competition among educational institutions. Specific Background: School promotion communicates educational services, while school image reflects perceived quality, reputation, values, and identity. Knowledge Gap: Previous studies have often examined promotion and school image separately, with limited evidence from the social and cultural context of Merauke. Aims: This study examines promotion and school image in parents’ decisions to choose SMP Muhammadiyah Merauke. Results: A quantitative survey of 123 seventh-grade parents was analyzed using simple and multiple linear regression. Promotion was not statistically significant (p = 0.334), whereas school image was significant (p = 0.000; B = 0.694). Simultaneously, both variables explained 55.6% of decision variance (R² = 0.556). Novelty: The study examines both variables simultaneously in a 3T border-region context. Implications: School management should prioritize service quality, institutional reputation, and contextually relevant communication. Key Findings Highlights Promotion was not statistically significant individually (p = 0.334). Institutional image showed a significant coefficient of B = 0.694. The joint model explained 55.6% of decision variance. Keywords: School Image, School Promotion, Parents’ Decision, Educational Marketing, School Selection